1996
DOI: 10.1111/j.1945-5100.1996.tb02015.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural outer rim of Chesapeake Bay impact crater: Seismic and bore hole evidence

Abstract: Abstract— Nine seismic‐reflection profiles and four continuous core holes define the gross structural and stratigraphic framework of the outer rim of the Chesapeake Bay impact crater. The rim is manifested as a 90 km diameter ring of terraced normal‐fault blocks, which forms a ∼320 m–1200 m high rim escarpment. The top of the rim escarpment is covered by a 20 m–30 m thick ejecta blanket. The escarpment encircles a flat‐floored annular trough, which is partly filled with an ∼250 m thick breccia lens (Exmore bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 20 publications
5
58
2
Order By: Relevance
“…In contrast, Sharpton et al [1993,1996] analyzed gravity and core data from which they inferred a Df of 260-300 km and a minimum Dte of 120 km and a Sharpton et al [1996] as well, it has never been conclusively demonstrated that the major gravity feature at Chicxulub must correlate with the final crater rim. For example, the major gravity anomaly in the -•90 km diameter Chesapeake Bay crater lies well within the crater rim [Poag, 1996], which was also formed in sedimentary rocks like Chicxulub. Hildebrand et al [1995] equate the location of the transient crater rim with a gravity low that they interpret as the peak ring at a radius of 40-45 km.…”
Section: Crater Sizementioning
confidence: 99%
“…In contrast, Sharpton et al [1993,1996] analyzed gravity and core data from which they inferred a Df of 260-300 km and a minimum Dte of 120 km and a Sharpton et al [1996] as well, it has never been conclusively demonstrated that the major gravity feature at Chicxulub must correlate with the final crater rim. For example, the major gravity anomaly in the -•90 km diameter Chesapeake Bay crater lies well within the crater rim [Poag, 1996], which was also formed in sedimentary rocks like Chicxulub. Hildebrand et al [1995] equate the location of the transient crater rim with a gravity low that they interpret as the peak ring at a radius of 40-45 km.…”
Section: Crater Sizementioning
confidence: 99%
“…About one-third of the presently known impact structures are subsurface (Grieve, 1991(Grieve, , 1997Grieve andMasaitis, 1994;Grieve et aL, 1995); (Canada) (Jansa andPe-Pipe,;]. Several large and relatively young buried impact structures have also been identified by geophysical techniques: the 90-km-diameter Chesapeake Bay Crater (USA) (Poag, 1996(Poag, , 1997; the larger (>180-kin diameter) Chicxulub structure (Mexico), which is associated with the K/T event (Hildebrand et aL, 1991;Sharpton et al, 1992;papers in Ryder et al, 1996); and the large (->70 km?) Morokweng structure (South Africa) (Corner et aL, 1997;Koeberl et al, 1997a).…”
Section: Suevite Breccia _ Fracturesmentioning
confidence: 99%
“…If th : crater remains below the water level, it will immediately begin to fill with sediments, and its subsequent history will _.epend on whether it remains below water level (continuous sediment filling) or is uplifted at some future time (begim ing of erosion). A number of such submarine impact struc ures have now been recognized; some have subsequently be en raised above sea level [e.g., Lockne (Sweden) (Therrk ult and Lindstrom, 1995;Lindstro'm et al, 1996)] and others still remain buried [e.g., Montagnais (Canada) (Jansa and t¥-PiDer, 1987); the Chesapeake Bay Crater (USA) (Poag, 1996(Poag, , 1997; and the recently discovered Mjolnir structure (Norway) in the Barents Sea (DyDvik et al, 1996)]. …”
Section: Multiring Basinsmentioning
confidence: 99%
See 2 more Smart Citations